IMPACT OF THE N-POWER PROGRAM ON POVERTY ALLEVIATION IN ENUGU STATE, NIGERIA (2016-2020) - Chika Olorunfemi, Glory; Samson Egwuma, Ojiakor (African Journal of Social and Behavioural Sciences, 2024)
This study examined the effect of n-power program on poverty alleviation in Nigeria; a study Enugu state, 2016 - 2020. The study sought to assess how N-Power programme of President Mohammadu Buhari administration had achieved its target of poverty alleviation in Enugu state between 2016 – 2020 and examine the constraints that undermine N-power programme in poverty alleviation in Enugu State. The study was descriptive and relied on secondary sources of data collection and used content analysis to analyze its data. The study found among others, that N-Power programme has assuaged unemployment, built capacities of young graduates, increased disposable income, stimulated economic value chain and has enhanced investment of youths in within the period of 2016- 2020. While it was challenged by decentralization of authority, correct BVN information, objective decision on recruitment, selection of candidates with requisite training and conversion of N-Power beneficiaries to permanent staff would make N-Power programme formidable for reduction of unemployment in Nigeria. The study recommended that government should endeavour to make N-Power job permanent, candidates with skills and knowledge into N-Power programme and that government should decentralize N-Power programme to both state and local government levels, equally, beneficiaries should endeavour to submit correct BVN to the management of N-Power for easy payment of stipends. All these can enhance N-Power to alleviate poverty in Enugu state.